Association between blood pressure control during aneurysm clipping and functional outcomes in patients with aneurysmal subarachnoid hemorrhage - Han, Xiangning; Luo, Guogang; Li, Jiahao; Liu, Rui; Zhu, Ning; Jiang, Shiliang; Ma, Wenlong; Cheng, Yawen; Liu, Fude (Frontiers in Neurology, 2024)
Objectives We explored the relationship between blood pressure variability (BPV) during craniotomy aneurysm clipping and short-term prognosis in patients with aneurysmal subarachnoid hemorrhage to provide a new method to improve prognosis of these patients. Methods We retrospectively analyzed the differences between patient groups with favorable modified Rankin Scale (mRS ≤ 2) and unfavorable (mRS > 2) prognosis, and examined the association between intraoperative BPV and short-term prognosis. Results The intraoperative maximum systolic blood pressure (SBPmax, p = 0.005) and the coefficient of variation of diastolic blood pressure (DBPCV, p = 0.029) were significantly higher in the favorable prognosis group. SBPmax (OR 0.88, 95%CI 0.80–0.98) and Neu% (OR 1.22, 95%CI 1.03–1.46) were independent influence factors on prognosis. Patients with higher standard deviations of SBP (82.7% vs. 56.7%; p = 0.030), DBP (82.7% vs. 56.7%; p = 0.030), and DBPCV (82.7% vs. 56.7%; p = 0.030) had more favorable prognosis. Conclusion Higher SBPmax (≤180 mmHg) during the clipping is an independent protective factor for a 90-day prognosis. These results highlight the importance of blood pressure (BP) control for improved prognosis; higher short-term BPV during clipping may be a precondition for a favorable prognosis.